Perkembangan Penelitian Mikroplastik di Indonesia - Alam, Firdha Cahya; Rachmawati, Mulki (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2020)
Microplastics are plastic particles that have a diameter less than 5 mm. Research related to microplastics has developed in the world as well as in Indonesia. Research in Indonesia has been carried out in various places on the islands of Sumatra, Java, Kalimantan, Sulawesi and Papua. However, there has been no study of the current development status of microplastic research in Indonesia. This paper describes the development of microplastic research in Indonesia from 2014 to 2020 using a systematic review method. The results of the review show that the majority of research on microplastics in Indonesia is about the distribution of microplastics, both in freshwater, marine, and in organisms. In terms of location, the majority of research on microplastics was in Java (66.67%), with the most common form of microplastics being fiber, compared to other forms. In addition, various microplastic concentrations were obtained from various locations. However, the concentrations obtained cannot be directly compared, because the sampling method used is different from one location to another. This is because the microplastic sampling method has not been standardized.